PROBLEMATIKA MANAJEMEN KELAS DI INTERNATIONAL CLASS PROGRAMME MTS. HASAN JUFRI KEBUNAGUNG LEBAK SANGKAPURA GRESIK - Mohammad Adnan (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2016)
The problems of classroom management are all kinds of problems that occur during the process of classroom management, both issues that arise from the material element (educational facilities) or problems arising from the human element (students and teachers). To deal with the problems that occur when managing a classroom, there are two treatment that can be done, which is preventive handling (preventing) and curative handling (treatment). The research location is excellent class of International Class Programme (ICP) of MTs. Hasan Jufri Sangkapura-Bawean-Gresik. The authors found (1). 10 kinds of classroom management problems in ICP MTs. Hasan Jufri. The problem sometimes comes from the students, for example, students in violation of the established rules, and sometimes come from the teacher, for example, teachers go to class late, and sometimes originates from a facility, such as air vents that make the classroom atmosphere uncomfortable. (2). efforts made to address the problem, using the preventive and curative handling. Preventive handling to prevent and minimize the problems that will occur, for example, set the rules, giving the appeal and so on. While curative handling is done to resolve the problems that have occurred that are not sustainable, for example, impose penalties teacher cleaning offices, or pay fines and other matters that are considered useful and can solve the problem.